Ilustrated Versión of the Law # 693 The Law of Sovereignty Food Security and Nutrition - Zeledón Zeledón, Dora Odely
Bibliografia- The National Assembly of Republic of Nicaragua presents to hhe citizenship the ilustrated version of the law No. "Law of sovereigty and Food security and Nutrition